1993
DOI: 10.1351/pac199365030409
|View full text |Cite
|
Sign up to set email alerts
|

New frontiers in host-guest chemistry: The gas phase

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 0 publications
0
40
0
Order By: Relevance
“…This special affinity in the condensed-phase has been attributed to a variety of factors including the "best-fit" phenomena [5] between K + and the 18c6 cavity. However, initial gas phase studies [6,7] of alkali metal ion:18c6 complexes did not replicate this selective behavior of 18c6 for K + . Experimental [8,9] and computational [10] studies showed that the effect of microhydration was crucial in bridging the gap between the gas phase and the condensed phase.…”
Section: Introductionmentioning
confidence: 91%
“…This special affinity in the condensed-phase has been attributed to a variety of factors including the "best-fit" phenomena [5] between K + and the 18c6 cavity. However, initial gas phase studies [6,7] of alkali metal ion:18c6 complexes did not replicate this selective behavior of 18c6 for K + . Experimental [8,9] and computational [10] studies showed that the effect of microhydration was crucial in bridging the gap between the gas phase and the condensed phase.…”
Section: Introductionmentioning
confidence: 91%
“…This article intends to review the progress made in the field of gas-phase studies of host-guest complexes and supramolecular assemblies (also, see : Brodbelt & Liou, 1993;Dearden et al, 1993;Vincenti et al, 1993Vincenti et al, , 1998Vincenti, 1995;Brodbelt, , 2000Brodbelt & Dearden, 1996;Dearden, 1996;Schalley, 2000). It also includes reports with a mass spectrometric focus, when solution-phase properties are analyzed by mass spectrometric methods.…”
Section: Benefits Of Mass Spectrometry For Supramolecular Chemistrymentioning
confidence: 99%
“…In addition, donor atoms such as nitrogen that have smaller electronegativity would cause lower dipole-ionic interaction towards the cations, consequently aza-crown ethers that possess nitrogen within the cavity would have weaker retention of the cations and thus resulting in the lower separation efficiency when compared to the typical crown ether, i.e. 2AM18C6 [15][16].…”
Section: Effect Of Eluent On the Retention Of Analyte Anionsmentioning
confidence: 99%